The Using of Distance Learning (Online) to Students of SMP IT Alhijrah Bintuju - Nasution, Laswardi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research was carried out at SMP IT Alhijrah Bintuju. The aim of this research is to find out whether there is a significant influence of the application of distance learning techniques (online) on the ability to write procedure texts by class VII students at SMP IT Alhijrah Bintuju.This research is an experimental study with a population of class VII SMP IT Alhijrah Bintuju consisting of 1 class in which 28 students. Meanwhile, the sample for this research was class VII with a total of 28 students using total sampling techniques. The data from this research were obtained from test scores, namely a test of the ability to write procedure texts before using distance learning techniques (pre test) and a test of the ability to write procedure texts after using distance learning techniques (post test). The data obtained were analyzed using the t test formula.Based on the results of data analysis, the results obtained consist of: 1) The results of data calculations illustrate that the mean score for the ability to write procedure texts after using the distance learning technique (online) was obtained with a score of 78.04, in the